The administrator, teachers and parents involvement in preschool during Movement Control Order - Senin, Muhammad Adam; Halim, Harliana (UPSI, 2021)
The Covid-19 pandemic is affecting the whole education system including the preschoolers in Malaysia in receiving a proper teaching and learning lesson especially in the classroom. Movement Control Order (MCO) implemented by the government has restricted the act for each person in the daily life. However, the action and role that has been played by the preschool administrators, teachers and parents in ensuring the smoothness of the teaching and learning process of the preschoolers should be recognized. This study focuses on the responses and roles that have been conducted and given by the preschool management and teacher as well as parents in assisting their preschoolers children during the MCO period. This study also determined the reaction played by the preschoolers in adapting the new norm act according to the Standard Operating Procedures (SOP) given by the government. A qualitative research design by using observation and interview based on the responses given by ten randomly chosen among preschool parents, teachers and administrators in a government preschool in Johor, Malaysia were used in this study. Phenomenology research was conducted to investigate the experience that has been gone through by the informants of the study during the MCO period. Narrative writing analysis were used to explain the outcome. This study indicated that the preschool administrators and teachers were able to collaborate and conduct an excellent code of practice according to the SOPs given by the government. Meanwhile, parents were able to establish a strong communication with the administrators and teachers by following the SOPs and assist the preschool management in ensuring their children are following the new norm acts according to the SOPs. A strong collaboration between all parties involved has shown a good example to the preschoolers during the pandemic MCO period.